Verrucous carcinoma of the esophagus – a case report and literature review - Frieling, Thomas; Kreysel, Christian; Blank, Michael; Müller, Dorothee; Euler, P.; Melchior, Ilka; Wullstein, Christoph; Hemmerlein, Bernhard (Zeitschrift für Gastroenterologie, 2020)
Background Verrucous carcinoma of the esophagus is a rare disease leading to dysphagia, chest pain, and weight loss. The diagnosis is difficult because even repeated biopsies are often without tumor evidence. We present a patient with verrucous carcinoma of the esophagus and a literature review.Case report A 64-year-old patient with dysphagia and sore throat received esophagogastroduodenoscopy illustrating segmental circumferential verrucous inflammation and Candida esophagitis in the middle part of the esophagus. Repeated mucosal biopsies revealed reactive hyperkeratosis of the squamous epithelium with minimal atypia but without ulcera, eosinophilic esophagitis, or suspicion of cancer. Mucosal infection with adenovirus, herpes simplex virus 1, human papilloma virus types, and cytomegaly virus was ruled out. Veruccous carcinoma was detected finally by endoscopic mucosal resection. The patient was successfully treated by esophageal resection. Tumor stage was G1, pT1b, pN0, L0, V0, Pn0, R0.Conclusion The results suggest that macroscopic suspicion of verrucous esophageal carcinoma should lead to resections of larger tissue specimens by EMR to confirm the diagnosis.
Keywords: dysphagia; regurgitation; noncardiac chest pain; verrucous esophageal carcinoma